Whole-exome sequencing in patients with protein aggregate myopathies reveals causative mutations associated with novel atypical phenotypes - Machnicki, Marcin M.; Guglielmi, Valeria; Pancheri, Elia; Gualandi, Francesca; Verriello, Lorenzo; Pruszczyk, Katarzyna; Kosinska, Joanna; Sangalli, Antonella; Rydzanicz, Malgorzata; Romanelli, Maria Grazia; Neri, Marcella; Ploski, Rafal; et al. (Neurological sciences, 2021)
Background Myofibrillar myopathies (MFM) are a subgroup of protein aggregate myopathies (PAM) characterized by a common histological picture of myofibrillar dissolution, Z-disk disintegration, and accumulation of degradation products into inclusions. Mutations in genes encoding components of the Z-disk or Z-disk-associated proteins occur in some patients whereas in most of the cases, the causative gene defect is still unknown. We aimed to search for pathogenic mutations in genes not previously associated with MFM phenotype. Methods We performed whole-exome sequencing in four patients from three unrelated families who were diagnosed with PAM without aberrations in causative genes for MFM. Results In the first patient and her affected daughter, we identified a heterozygous p.(Arg89Cys) missense mutation in LMNA gene which has not been linked with PAM pathology before. In the second patient, a heterozygous p.(Asn4807Phe) mutation in RYR1 not previously described in PAM represents a novel, candidate gene with a possible causative role in the disease. Finally, in the third patient and his symptomatic daughter, we found a previously reported heterozygous p.(Cys30071Arg) mutation in TTN gene that was clinically associated with cardiac involvement. Conclusions Our study identifies a new genetic background in PAM pathology and expands the clinical phenotype of known pathogenic mutations.